Health literacy and COVID-19 vaccine acceptance worldwide: A systematic review - Eneyew Talie Fenta; Misganaw Guadie Tiruneh; Amare Mebrate Delie; Atitegeb Abera Kidie; Birtukan Gizachew Ayal; Liknaw Workie Limenh; Beselam Gizachew Astatkie; Nigus Kassie Workie; Zeamanuel Anteneh yigzaw; Eyob ketema Bogale; Tadele Fentabil Anagaw (SAGE Open Medicine, 2023)
Objective: Health literacy helps an individual to have the capacity to obtain, process, and understand basic health information to make appropriate health decisions. This study aimed to review the association between health literacy and COVID-19 vaccine acceptance. Method: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses steps. Databases including PubMed/MEDLINE, Web of Science, Scopus, EMBASE, World Health Organization libraries, and Google Scholar were used to search all published articles in the area of health literacy and COVID-19 vaccine acceptance until August 1, 2022. Result: In this review, 1348 articles were retrieved. Finally, 13 articles were included in the review after the removal of duplicates that did not meet our inclusion criteria. In all, 10 articles showed that health literacy was significantly associated with COVID-19 vaccine acceptance. This review also showed that positive perception of the vaccine, vaccine hesitancy, adverse reaction from vaccines, residence, socioeconomic status, level of education, younger age, being a health worker, and positive belief have associations with health literacy and COVID-19 vaccine acceptance. There was significant heterogeneity in the study population and measurement tools used for health literacy and COVID-19 vaccine acceptance. Conclusion: This systematic review provides comprehensive evidence on health literacy and COVID-19 vaccine acceptance globally. There was significant heterogeneity in the study population and measurement tools used for health literacy and COVID-19 vaccine acceptance. Most studies reported that health literacy is significantly associated with COVID-19 vaccine acceptance. Therefore, investing in health literacy using different vaccine promotion strategies may improve COVID-19 vaccine acceptance and health decision-making to decrease the impact of the COVID-19 pandemic.